2012
DOI: 10.1111/j.1750-3841.2012.02746.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of UV‐C Treatments to Maintain Quality and Extend the Shelf Life of Green Fresh‐cut Bell Pepper (Capsicum annuum L.)

Abstract: Exposure to UV-C radiation before packing and refrigeration could be a useful nonchemical alternative to maintain quality and reduce postharvest losses in the fresh-cut industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 32 publications
3
19
0
1
Order By: Relevance
“…Shortwave ultraviolet light, 200 to 280 nm (UV‐C) radiation has been reported to be successful in reducing the number of surface microorganisms of fresh and cut fruits and vegetables (Yaun ; Fonseca and Rushing, ; Shama ; Rodoni and others ). Although the effects of UV‐C treatments on fruit juices have been widely studied, studies on its effect on fresh‐cut fruits remain scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Shortwave ultraviolet light, 200 to 280 nm (UV‐C) radiation has been reported to be successful in reducing the number of surface microorganisms of fresh and cut fruits and vegetables (Yaun ; Fonseca and Rushing, ; Shama ; Rodoni and others ). Although the effects of UV‐C treatments on fruit juices have been widely studied, studies on its effect on fresh‐cut fruits remain scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Fruits that were exposed to UV‐C were found to exhibit delayed ripening, delayed senescence as well as reduced spoilage . Several researchers have reported on the immediate effects of UV‐C treatment on the quality of fruits while the underlying changes at a proteomic level that occurs as a result of UV‐C irradiation remains unclear . UV‐C irradiation has been known to cause either generation of reactive species, which results in protein thiol oxidation, or protein damage through photolysis.…”
Section: Introductionmentioning
confidence: 99%
“…UV‐C treatment has been reported to be effective in controlling postharvest diseases in fruits (González‐Aguilar and others ; Cia and others ; Janisiewicz and Conway ; Andrade Cuvi ; Rodoni ). In this study, it was found that UV‐C treatment alone effectively controlled postharvest diseases of jujube fruits caused by A. alternata .…”
Section: Discussionmentioning
confidence: 99%